Allocation of Funds by Beneficiaries of the Family Hope Program for the Economic Independence of the Patila Community, North Luwu Regency - Anita Sari; Fahira Herawati; Mursyid Mursyid (Dinamis : Journal of Islamic Management and Bussiness, 2022)
This study aims to find out how to allocate funds for the Family Hope Program for economic independence in Patila, North Luwu Regency. The author uses data collection techniques through interviews, documents and documentation. By using this type of qualitative research using data collection methods carried out directly in the field (object of research). Subjects taken as respondents were 10 respondents who developed their business. Sources of data include primary data and secondary data. Primary data can be obtained through interviews with respondents.